Cho \(F\left( x \right) = \left( {x - 1} \right){e^x}\) là một nguyên hàm của hàm số \(f\left( x \right){e^{2x}}\). Tìm nguyên hàm của hàm số \(f'\left( x \right){e^{2x}}\).
A.\(\int {f'\left( x \right){e^{2x}}} {\rm{d}}x = \left( {x - 2} \right){e^x} + C\)
B.\(\int {f'\left( x \right){e^{2x}}} {\rm{d}}x = \dfrac{{2 - x}}{2}{e^x} + C\)
C.\(\int {f'\left( x \right){e^{2x}}} {\rm{d}}x = \left( {2 - x} \right){e^x} + C\)
D.\(\int {f'\left( x \right){e^{2x}}} {\rm{d}}x = \left( {4 - 2x} \right){e^x} + C\)

Các câu hỏi liên quan